STUDENTS’ PERCEPTION ON LEARNING READING COMPREHENSION THROUGH RECIPROCAL TEACHING STRATEGY - Mardhiyatu Zakiyah; Maya Rahmawati; Iwan Ridwan (STKIP Siliwangi, 2021)
Students encountered several problems when trying to master a reading skill. Reciprocal teaching strategy was known as a guided comprehension strategy that encouraged the students to develop the skills that effective readers and learners did. This research aimed to investigate the perception of twelve students of Islamic senior high school toward reading utilizing reciprocal teaching strategy in terms of cognitive and affective aspects. It was carried out as a qualitative descriptive. The data were collected through observation, semi-structured interview, and open-ended questionnaire. The data were analyzed by using Braun and Clarke’s theory such as read, transcript, code, categorize and interpret the data. The results indicated that based on cognitive aspect, the students had positive responses such as reciprocal teaching facilitated readers to understand some texts, increased their capabilities to answer and ask the questions, estimated what the author means, encouraged them to think rationally, explained the new word, and summarized the next scene. Furthermore, the data also showed that the reciprocal teaching strategy had a positive response based on affective aspect such as supporting students to cope with difficulties during reading. Keywords: Reciprocal teaching strategy, Perception, Cognitive aspect, Affective aspect.